Modelling the human cardiac fluid mechanics. 3rd ed - Oertel, HerbertKrittian, SebastianSpiegel, Kathrin (KIT Scientific Publishing, 2009)
The third edition of this article on the modelling and simulation of the flow in human hearts supplements earlier editions. It discusses the flow-structure coupled heart model KAHMO FSI (Karlsruhe Heart Model) and examines patient-specific clinical application of the heart model for cardiac surgery. The KAHMO heart model can be used to predict flow losses and flow structures due to pathalogical ventricle defects. These are considered before and after surgery.